Perancangan dan Pengembangan Smart Pet Feeder dengan Aplikasi Mobile Blynk dan ESP8266 - Haris Sulthan; Jerry Beltsazar Nainggolan; Muhammad Rafli Alamsyah; Mohammad Rabby Afrizie; Andik Yulianto (Telcomatics, 2026)
This research presents the design and development of a Smart Pet Feeder system based on the Internet of Things (IoT) using the Blynk platform to simplify pet feeding management. The primary goal of this system is to ensure consistent feeding schedules, reduce manual intervention, and provide remote control and monitoring capabilities. The system utilizes the ESP8266 microcontroller integrated with a load cell sensor and servo motor to dispense pet food accurately. Real-time data on remaining food levels is transmitted to the Blynk Cloud, allowing users to monitor food stock, schedule feeding times, and receive notifications when the stock is running low.The methodology involves a multi-layer communication architecture: perception layer for data acquisition, communication layer for connectivity, data processing layer for cloud-based analysis, and application layer for user interaction. The load cell measures food weight, while the servo motor dispenses food based on user input via the Blynk interface. The implementation results demonstrate that the system effectively reduces manual feeding tasks, prevents overfeeding, and optimizes food efficiency. This innovative approach not only enhances convenience for pet owners but also promotes sustainable pet care practices by ensuring precise and timely feeding.